General metadata for the Phillimore notes - various (The University of Hull)
The County Notes provide a discussion on all matters of interest or obscurity in the text, in the light of the latest Domesday scholarship. Such matters vary from county to county but recurrent topics include: the identification of place-names, personal names, and individuals; the meaning of obscure Latin words or phrases, or of ambiguous formulae; uncommon data; curious statistics; relevant material from related sources, including Domesday 'satellite' texts where relevant; variants in other editions; the state of the manuscript, including the work of individual scribes, insertions, amendments, and scribal conventions; misreadings in Domesday facsimiles; material bearing on larger Domesday topics, such as the Domesday Inquest and the date and compilation of Domesday Book; and all other items of interest. The Notes are based on the original printed edition published by Phillimore (1975-86) by a variety of editors; the Notes for eight counties have been thoroughly revised and greatly enlarged for this edition by Caroline and Frank Thorn, and the remainder lightly revised, with the addition a number of new entries.